A study on factors influence Bachelor of Administrative Science final year students in selecting research supervisor for ADS 511 in UiTM Kampus Bandaraya Melaka / Nurhazirah Zulhaimy and Nur Amirah Tukimin - Zulhaimy, Nurhazirah; Tukimin, Nur Amirah (Faculty of Administrative Science and Policy Studies, 2014)
In this study, the researcher is focus on the factors that influence Bachelor of Administrative Science final year students in selecting research supervisor for ADS 511 in UiTM Kampus Bandaraya Melaka. The purpose of the study is to examine whether there is any relationship between students and selecting the supervisor among students in UiTM Kampus Bandaraya Melaka and to identify which factor most influence students in selecting their supervisor. This research emphasizes on the purpose of conducting by examining how several factors lead to the selecting supervisor among students. Besides that, in this study it focus on three factors which are teaching style, lecturer personality and lecturer expert. For this study, the researcher uses the simple random sampling and from 260 populations the sampling is 155 respondents. In this research also use several methods such as reliability test, normality test, the Pearson Correlation and also multiple regression analysis. The findings show that higher number of respondents answered the questionnaire were females. Based on the multiple regressions, it indicates that teaching style is the most factor influence in selecting supervisor and the lowest factors is lecturer personality that influence students in selecting their supervisor in UiTM Kampus Bandaraya Melaka.